Factores de riesgo asociados a la prevalencia de enteroparásitos en niños de 1 a 7 años de edad atendidos en el Hospital Distrital Santa Isabel, El Porvenir - Trujillo, agosto – diciembre, 2021 - Vásquez Romero, Delia Katheryn (2023)
In Peru, as in Latin America, intestinal parasitosis is a public health problem due to its high prevalence in the child population (80%), mainly caused by inadequate hygienic conditions, so the objective of this study was to determine the relationship that exists between the risk factors and the prevalence of enteroparasites in children from 1 to 7 years of age treated at the Santa Isabel District Hospital, El Porvenir-Trujillo, during the period august - december, 2021. A cross-sectional descriptive study was carried out, with a non-probabilistic sample for convenience in children taken to outpatient clinics; A socio-epidemiological survey was applied to parents or guardians with prior informed consent and three stool samples were requested for parasitological examination; the degree of association between the risk factors was evaluated through the Odds ratio (OR). It was found that 54.2% of the examined children were positive for the presence of intestinal parasites, being Blastocystis sp. the most frequent (57.7%) as well as monoparasitism (96.2%); The risk factors associated with enteroparasitosis in the study population were onychophagy with a value of OR=3.044 (IC=1.401-6.610, p=0.005), overcrowding with an OR=2.136 (IC=1.258-3.628, p =0.005) and the ownership of domestic animals. It is concluded that onychophagy, overcrowding and ownership of domestic animals are risk factors associated with parasitism in children from 1 to 7 years of age.